Analysis of Cell Wall-Related Genes in Organs of Medicago sativa L. under Different Abiotic Stresses - Behr, Marc (Int J Mol Sci, 2015)
Abiotic constraints are a source of concern in agriculture, because they can have a strong impact on plant growth and development, thereby affecting crop yield. The response of plants to abiotic constraints varies depending on the type of stress, on the species and on the organs. Although many studies have addressed different aspects of the plant response to abiotic stresses, only a handful has focused on the role of the cell wall. A targeted approach has been used here to study the expression of cell wall-related genes in different organs of alfalfa plants subjected for four days to three different abiotic stress treatments, namely salt, cold and heat stress. Genes involved in different steps of cell wall formation (cellulose biosynthesis, monolignol biosynthesis and polymerization) have been analyzed in different organs of Medicago sativa L. Prior to this analysis, an in silico classification of dirigent/dirigent-like proteins and class III peroxidases has been performed in Medicago truncatula and M. sativa. The final goal of this study is to infer and compare the expression patterns of cell wall-related genes in response to different abiotic stressors in the organs of an important legume crop.